Repetitive restenosis in a biodegradable polymer sirolimus-eluting stent with hypersensitivity reaction: a case report. Issue 1 (4th February 2020) - Jimba, Takahiro; Hashikata, Takehiro; Matsushita, Masashiro; Yamasaki, Masao
Abstract: Background : Hypersensitivity reaction is a classic cause of in-stent restenosis (ISR) in coronary stents, typically reported in bare-metal stents and first-generation drug-eluting stents. Biodegradable polymer sirolimus-eluting stent (BP-SES) was developed with the concept of biocompatibility, and there has been no report of ISR of BP-SES with hypersensitivity reaction. Case summary : An 81-year-old woman presented with ST-elevation acute inferior myocardial infarction. Primary percutaneous coronary intervention was performed for the culprit lesion in the left circumflex artery with a permanent polymer everolimus-eluting stent (PP-EES), followed by BP-SES implantation in the left anterior descending artery. Eight months later, coronary angiography showed total occlusion of the PP-EES and diffuse ISR in the BP-SES, treated with a paclitaxel-eluting balloon. Fluorodeoxyglucose with positron emission tomography showed increased uptake around the BP-SES, and cardiac magnetic resonance imaging revealed a late gadolinium-enhanced area around both stents. Four months later, she developed re-ISR in the BP-SES, and optical coherence tomography demonstrated diffuse-layered neointimal hyperplasia with microvascularization and peri-strut low-intensity area. She was successfully treated with coronary artery bypass grafting. Discussion : Our case demonstrated repetitive short-term ISR of the BP-SES. Observation by both intravascular and non-invasive imaging modalities suggested the presence of hypersensitivity reaction localized in the stent. Hypersensitivity to the metal may be a possible mechanism because both stents are composed of L605 cobalt–chromium alloy. This is the first report of ISR of a BP-SES with hypersensitivity reaction. Non-invasive imaging can be useful to assess this critical condition.